MOTHER AND CARRIER: PHENOMENOLOGY STUDY OF DUAL-CARRIER FAMILY - Subhan Ajrin (Universitas Islam Negeri Imam Bonjol Padang, 2014)
Mother with dual-career family has a dual role to be performed at the same time. Therefore, as a mother with double plays in a dilemma between family and career interests. Data collection using